Genome maintenance and transcription integrity in aging and disease - Wolters, Stefanie; Schumacher, Björn (Frontiers in Genetics, 2013)
DNA Damage contributes to cancer development and ageing. Congenital syndromes that affect DNA repair processes are characterized by cancer susceptibility, developmental defects, and accelerated ageing (Schumacher et al., 2008). DNA damage interferes with DNA metabolism by blocking replication and transcription. DNA polymerase blockage leads to replication arrest and can gives rise to genome instability. Transcription, on the other hand, is an essential process for utilizing the information encoded in the genome. DNA damage that interferes with transcription can lead to apoptosis and cellular senescence. Both processes are powerful tumor suppressors (Bartek and Lukas, 2007). Cellular response mechanisms to stalled RNA polymerase (RNAP) II complexes have only recently started to be uncovered. Transcription-coupled DNA damage responses might thus play important roles for the adjustments to DNA damage accumulation in the ageing organism (Garinis et al., 2009). Here we review human disorders that are caused by defects in genome stability to explore the role of DNA damage in ageing and disease. We discuss how the nucleotide excision repair (NER) system functions at the interface of transcription and repair and conclude with concepts how therapeutic targeting of transcription might be utilized in the treatment of cancer.